INFLUENCE OF VARIOUS WEED MANAGEMENT PRACTICES ON WEEDS AND YIELD COMPONENTS OF PEA (PISUM SATIVUM L.) - ABDULLAH, .; KHAN, YSA; KHAN, R; KHAN, M; ZAFAR, MH; KALSOM, A; SHAHZAD, S; TALHA, A; JAVED, A; SHOAIB, M (Biological and Clinical Sciences Research Journal, 2024)
A field experiment was conducted throughout the winter cropping season of the year 2018, at the New Developmental Research Farm (NDRF), the University of Agriculture-Peshawar, to assess the efficiency of techniques for weed control on weed suppression, and yield components of edible pea. The research was designed, using a Randomized Complete Block Design, with 13 treatments, which were repeated 3 times. The applied treatments comprised; Mulches (Eucalyptus leaves, weed biomass, and poplar leaves), herbicides (S-metolachlor, Pendimethalin, Haloxyfop-p-methyl, and Quizalofop-p-ethyl), and hand-weeded plots (hand weeding at 20 DAS, hand weeding at 40 DAS, hand weeding at 60 DAS, and two times hand weeding at 30 and 60 DAS), weed-free, and weedy check(untreated). Parameters documented included; weed density (m-²), fresh biomass (kg ha-¹), seeds pod-1, hundred seed weight (g), seed yield (kg ha-¹), and CBR. Based on our outcomes, the weedy check, had the highest weed density (40.1 m-²), and fresh biomass (441.67 kg ha-¹), whereas the weed-free treatment had the lowest values for both parameters. Likewise, in terms of agronomic parameters, the weed-free treatment produced the highest seeds (8.10 pod-1), hundred seed weight (53.33 g), and seed yield (4352 kg ha-¹). While, the weedy check treatment, exhibited the lowest values for these parameters. The use of Pendimethalin produced the highest cost-benefit ratio (CBR), while hand weeding and mulching produced the lowest CBR. These findings suggest that of various weed control methods, twice hand weeding, and the application of Pendimethalin, and S-metolachlor are effective for controlling weeds, and enhancing yield-related traits of pea.